מהו ההופך של g (x) = (x + 8) / 3?

מהו ההופך של g (x) = (x + 8) / 3?
Anonim

תשובה:

# g ^ -1 (x) = 3x - 8 #

הסבר:

תן #y = g (x) #. לכן, #y = (x + 8) / 3 #

# 3y = x + 8 #

#x = 3y - 8 #

# g ^ -1 (y) = 3y - 8 #.

לכן, # g ^ -1 (x) = 3x - 8 #

אם רצינו, נוכל להוכיח זאת תחילה # גרם # הוא בלתי הפיך, על ידי מראה כי עבור כל # x_1, x_2in #, איפה # A # הוא התחום של # גרם #, #g (x_1) = g (x_2) #

# x_1 = x_2 #, לכן # x_1 + 8 = x_2 + 8 # ו # (x_1 + 8) / 3 = (x_2 + 8) / 3 #

הוא טוען שאם # x_1 = x_2 #, #g (x_1) = g (x_2) #.

לפיכך, # גרם # הוא בלתי הפיך.